اقامت دین اور مدافعانہ منہج :ابلاغی مکتبہ فکر کا تعارف و تجزیہ: Establishing the Religion and the Defensive Approach: Introduction and Analysis of the Communicative School of Thought - Hafiz Abu Bakar Idrees; Hafiz Masood ur Rahman khan (AL-IDRAK JOURNAL, 2024)
This study focuses on the concept of "Iqamat al-Din" (establishing the religion) and its relationship with a defensive approach, analyzing the communicative school of thought in Islam. Iqamat al-Din refers to the effort to establish the foundational principles of Islam in society, encompassing spiritual, ethical, and societal aspects of life. This study examines the intersection of establishing the religion with a defensive approach, which is characterized by responding to external challenges to Islam while preserving its core values and teachings. The communicative school of thought in Islamic discourse emphasizes dialogue, interaction, and defense of the religion through intellectual and social engagement, rather than through aggression. This approach advocates for defending the truth of Islam by engaging with contemporary challenges, misconceptions, and critiques from other ideologies or belief systems. The communicative school emphasizes the importance of reason, wisdom, and knowledge in addressing doubts about Islam, aiming to strengthen its position in modern discourse. This research also delves into the practical applications of the communicative school of thought in contemporary contexts, evaluating its effectiveness in promoting a peaceful understanding of Islam in the face of global challenges. The study highlights the importance of a balanced and peaceful approach in defending the religion, and the potential for using communication as a tool for fostering better interfaith and intercultural dialogue in the modern world.